Robust Image Based Visual Servoing of Omnidirectional Mobile Manipulator - Jo, Kangmin; Chwa, Dongkyoung (Transactions of the Korean Institute of Electrical Engineers, 2022)
This paper proposes robust image based visual servoing of an omnidirectional mobile manipulator using integral sliding mode control to compensate for the uncertainty that may occur while performing the image-based visual servoing. The stability of the overall omnidirecitonal mobile manipulator system using the proposed method is proven by the Lyapunov stability analysis by showing that the error stays on the sliding surface always and asymptotically converges to zero. In order to solve the singularity problem that can occur when controlling the omnidirectional mobile robot and the manipulator at the same time, a switching technique is proposed in such a way that the omnidirectional mobile robot and manipulator operate sequentially to prevent the abnormal operation of the manipulator and solve the singularity problem. The validity of the proposed robust image based visual servoing method is verified through simulation results.
Keywords: Image based visual servoing; Integral sliding mode control; Lyapunov stability analysis; Mobile manipulator system; Omnidirectional mobile manipulator; Omnidirectional mobile robot; Singularity; Singularity problems; Sliding surface; Uncertainty; Image-based visual servoing; Integral sliding mode control; Omnidirectional mobile manipulator; Singularity